PENINGKATAN KADAR EUGENOL PADA MINYAK ATSIRI CENGKEH DENGAN METODE SAPONIFIKASI-DISTILASI VAKUM - Machmud Lutfi H; Wisnu Jati N; Aprilina Purbasari (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2013)
The purpose of this research is to study the saponification and vacuum distillation process to isolate eugenol from clove essential oils and get the optimum condition from this process.Eugenol is a compound that is used in many industries, such as perfume, flavouring, pesticides and anesthetic. In this era, the clove essential oils are available in market including 70% of eugenol. But the industry needs more than 90% eugenol included. So, we need the efficience process to increase its purity. And the process we use in this research is saponification-vacuum disltilation. The experimental design used in this research is the variation of NaOH normality and the temperature operation of distilllation.The NaOH normalities are from 0,3 to 1,2 N, and the temperature operation of distilllation are 170 o, 195 o, 220o C. The procedure of this research is mixing 70% clove essential oils with NaOH . After the solution has became homogeneous, let it stand into two layers, water and Na-eugenol. Separate the organic layer, and add HCl to the Na-eugenol till the pH down into 3-4. And then separate them. The higher layer that is 80 % eugenol is entered to the distilation tube. Run the distilation process with fixed temperature and vacuum pressure (6x10-2 kPa). After distillation process we got the weightest mass of eugenol at the temperature 220o C that the mass is 33,13 grams and the percentages of the mass is 89,65%.